2014
DOI: 10.1080/09658211.2013.872279
|View full text |Cite
|
Sign up to set email alerts
|

Wakeful rest alleviates interference-based forgetting

Abstract: Retroactive interference -the disruptive influence of events occurring after the formation of a new memory -is one of the primary causes of forgetting. Placing individuals within an environment that postpones interference should therefore greatly reduce the likelihood of information being lost from memory. For example, a short period of wakeful rest should diminish interference-based forgetting. To test this hypothesis, participants took part in a foreign language learning activity and were shown English trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 42 publications
4
55
3
Order By: Relevance
“…These findings stand in contrast to a number of previous studies investigating the resting effect under different experimental conditions (Brokaw et al 2016;Cowan et al 2004;Craig et al 2014Craig et al , 2015Della Sala et al 2005;Dewar et al 2009Dewar et al , 2012aMercer 2015), but support the results of recent studies, which showed that resting is no prerequisite for successful memory consolidation (e.g. Varma et al 2017).…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…These findings stand in contrast to a number of previous studies investigating the resting effect under different experimental conditions (Brokaw et al 2016;Cowan et al 2004;Craig et al 2014Craig et al , 2015Della Sala et al 2005;Dewar et al 2009Dewar et al , 2012aMercer 2015), but support the results of recent studies, which showed that resting is no prerequisite for successful memory consolidation (e.g. Varma et al 2017).…”
Section: Discussioncontrasting
confidence: 57%
“…Furthermore, it could be argued that a resting period of 8 min was too short. We assume that 8 min are adequate to detect an existing effect, since various studies found the resting effect over shorter (minutes to hours) and longer retention intervals (days) with varying post-learning resting periods between 8 to 12 min (Brokaw et al 2016;Craig et al 2014;Dewar et al 2012a, b;Mercer 2015). Furthermore, results of Dewar et al (2009) indicate that the first minutes after learning seem to be crucial for a memory supporting effect of resting.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…During an unfilled time interval, memory consolidation can be defined as an active process that works to strengthen a new memory trace so that it can be successfully retrieved at a later point in time (Dewar, Alber, Cowan & Della Sala, 2014;Mercer, 2015). Arguably, visual memoranda suffer from rapid time based decay if there is reduced opportunity for engaging in a consolidation process (Knöchel et al, 2015); as a result, the memory trace is more vulnerable to interference or overwriting from succeeding items (Nieuwenstein & Wyble, 2014, offer a recent test of so-called short-term TIME MANAGES INTERFERENCE 26 consolidation).…”
Section: Time For Consolidation?mentioning
confidence: 99%